2017
DOI: 10.1186/s12916-017-0852-2
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of low-density lipoprotein cholesterol estimation at very low levels

Abstract: BackgroundAs the approach to low-density lipoprotein cholesterol (LDL-C) lowering becomes increasingly intensive, accurate assessment of LDL-C at very low levels warrants closer attention in individualized clinical efficacy and safety evaluation. We aimed to assess the accuracy of LDL-C estimation at very low levels by the Friedewald equation, the de facto clinical standard, and compare its accuracy with a novel, big data-derived LDL-C estimate.MethodsIn 191,333 individuals with Friedewald LDL-C < 70 mg/dL, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 40 publications
(51 reference statements)
1
35
0
Order By: Relevance
“…Martin et al reported that among general subjects in the United States, LDL-C(M) showed good concordance with directly measured LDL-C at LDL-C level < 70 mg/dL compared with LDL-C(F) [LDL-C(M); 94.1%, LDL-C(F); 77.2%] 14 ) . Quisepe et al have also demonstrated that in patients with an LDL-C(F) level of 50–69 mg/dL, 29% of patients show LDL-C(D) level ≥ 70 mg/dL 16 ) . Furthermore, Meeusen et al pointed out that the discordance between LDL-C(F) and LDL-C( β Q), which is measured by β quantification and is considered the gold-standard method for determining LDL-C, was increased for LDL-C level < 70 mg/dL 15 ) .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Martin et al reported that among general subjects in the United States, LDL-C(M) showed good concordance with directly measured LDL-C at LDL-C level < 70 mg/dL compared with LDL-C(F) [LDL-C(M); 94.1%, LDL-C(F); 77.2%] 14 ) . Quisepe et al have also demonstrated that in patients with an LDL-C(F) level of 50–69 mg/dL, 29% of patients show LDL-C(D) level ≥ 70 mg/dL 16 ) . Furthermore, Meeusen et al pointed out that the discordance between LDL-C(F) and LDL-C( β Q), which is measured by β quantification and is considered the gold-standard method for determining LDL-C, was increased for LDL-C level < 70 mg/dL 15 ) .…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, Meeusen et al reported that LDL-C(F) underestimated LDL-C measured by β quantification [LDL-C( β Q)], which is considered the gold standard of LDL-C measurement, particularly in patients with LDL-C( β Q) < 70 mg/dL 15 ) . A recent study also demonstrated that LDL-C(M) by the Martin method correlated strongly with directly measured LDL-C(D), compared with LDL-C(F) at LDL-C < 40 mg/dL 16 ) . The validity of LDL-C(M) in different races and in patients with CVD, particularly with low LDL-C levels resulting from statin therapy, has not been elucidated.…”
Section: Introductionmentioning
confidence: 82%
“…However, this calculation is not valid for those with high triglycerides or very low LDLc 11. A novel estimate of LDL has been developed that shows good correlation with ultra-centrifugation and more precision than Friedwald across different ranges of triglycerides but also at very low LDL.…”
Section: Who Should Be Offered Lipid Testing?mentioning
confidence: 99%
“…This novel method has helped recategorize patients who were previously undertreated and is currently the method used for LDL-C estimation at multiple clinical laboratories [21]. However, the Martin-Hopkins equation was developed based on traditional linear regression analysis, and although it outperforms the Friedewald formula, there remain inaccuracies, especially at lower LDL-C estimates [22]. The accepted reference method for lipoprotein fraction measurement is the beta-quantification (BQ) method, which is possible in a limited setting but not suitable for mass screening due to its cost and labor-intensive nature.…”
Section: Introductionmentioning
confidence: 99%